2016
DOI: 10.1080/07448481.2016.1235578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of sexual assault among a college sample

Abstract: Objective This study examined the prevalence and correlates of sexual assault (SA) pre-college, college onset, and repeat SA within a representative student sample. Participants A representative sample of 7,603 students. Methods Incoming first year students completed a survey about their exposure to broad SA prior to college, prior trauma, personality, relationships, and mental health. Broad SA was then re-assessed each spring semester while enrolled. Results Nearly 20% of the sample reported experiencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
80
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 48 publications
17
80
1
1
Order By: Relevance
“…Consistent with previous research using the S4S sample (Conley et al 43 ), pre-college SA significantly predicted college-onset SA. This finding is consistent with a preponderance of literature suggesting that prior history of sexual assault is a strong predictor of subsequent sexual assaults 9 , particularly among college samples 11,12 .…”
Section: Commentsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with previous research using the S4S sample (Conley et al 43 ), pre-college SA significantly predicted college-onset SA. This finding is consistent with a preponderance of literature suggesting that prior history of sexual assault is a strong predictor of subsequent sexual assaults 9 , particularly among college samples 11,12 .…”
Section: Commentsupporting
confidence: 88%
“…Therefore, only individuals enrolled during the fall semester were included in the present analyses (N=6,132). Given that previous research using S4S data (e.g., Conley et al 44 ) has demonstrated high rates (around 20%) of SA, as well as a positive association between pre-college SA and college-onset SA, we sought to extend these findings to include potential factors that may explain this previously identified association. Additionally, the sample was representative of the broader university student population in terms of both gender and race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have confirmed the finding that students who were subjected to sexual violence in childhood or adolescence are more likely to experience sexual violence in college (Conley et al, 2017;Gidycz et al, 1993;Martin et al, 2011;Smith et al, 2003). Because most studies of campus sexual violence focus on college women, who are more likely than their male peers to be raped or assaulted (Cantor et al, 2015;Krebs et al, 2007Krebs et al, , 2016Smith-Marek et al, 2015), estimates of prior sexual victimization among college students generally describe women's experiences.…”
Section: Prevalence Of Prior Victimization and Sequelae Of Repeat Vicmentioning
confidence: 87%
“…The rate of sexual assaults on campuses has remained relatively unchanged over the past 20 years (Fedina, Holmes, & Backes, 2016). Conley et al (2017) asserted that sexual assault is the most common form of violence on college campuses, yet only about 12% are sexual assaults are reported (Coray, 2016). One in nine girls and one in 53 boys under the age of 18 experience sexual abuse or assault at the hands of an adult and females ages 16-19 are four times more likely than the general population to be victims of rape, attempted rape, or sexual assault (Finkelhor, Shattuck, Turner, & Hamby, 2014).…”
Section: Sexual Assault Preventionmentioning
confidence: 99%